Effects of a support group to self efficacy of breast cancer patients that receiving chemotherapy - Hanik Rohmah Irawati; Yati Afiyanti; Mondastri Korib Sudaryo (Faculty of Medicine, Universitas Islam Indonesia, 2019)
Background: The self-efficacy to cope with breast cancer patients can improve their adaptive coping skills, well-being and quality of life. Objective: This study aims to identify the effects of a support group to improve self-efficacy of breast cancer patients that receiving chemotherapy.Methods: This study used a quasy-experimental design with non-equivalent control pre-test post-test design. As much as 76 patients with breast cancer were assigned into either an experimental group or a control group (38 person each). All of them were selected through a consecutive sampling method. In addition, it used an instrument of cancer behavior inventory version 2. Results: Respondents who were supported by the support group had 1.4 times higher level of self-efficacy to cope with cancer than those who were not supported by a support group. No significant difference in the level of self-efficacy to cope with the cancer between the experimental group and the control group (RR 1.4 with 95% CI 1.0-1.8, a > 0.05).Conclusion: Supports provided by the support group had no effect on the level of self-efficacy to cope with the cancer.